Burnout, depression and anxiety among Swiss medical students – A network analysis. (November 2021) - Ernst, Jutta; Jordan, Katja-Daniela; Weilenmann, Sonja; Sazpinar, Onur; Gehrke, Samuel; Paolercio, Francesca; Petry, Heidi; Pfaltz, Monique C.; Méan, Marie; Aebischer, Oriane; Gachoud, David; Morina, Naser; et al.
Abstract: It is well established that burnout in medical students is associated with depression and anxiety at a syndromal level. Moreover, there is an ongoing debate about the extent to which burnout overlaps with depression and anxiety. The emerging network approach to psychopathology offers a new perspective on the interrelations between mental disorders focusing on symptom-level association. In this cross-sectional study, we exploratively investigated the associations among burnout, depression, and anxiety in 574 swiss medical students using a network analytic approach for the first time. Symptoms of depression and anxiety were assessed with the Patient Health Questionnaire and Generalized Anxiety Disorder respectively. Burnout was assessed with two single-item questions, one referring to emotional exhaustion and the other to depersonalization. We found a dense network in which at least one dimension of burnout was related to eleven of the sixteen included symptoms. This suggests that burnout is closely related to depression and anxiety but also has its own characteristics. Notably, suicidal ideation was not associated with either emotional exhaustion or depersonalization after adjusting for the influence of the remaining symptoms of anxiety and depression. Hence, the well-documented relationship between burnout and suicidal ideation in medical students may be entirely mediated by the experience of anxiety and depression. Hence, the well-documented relationship between burnout and suicidal ideation in medical students might be fully mediated by the experience of anxiety and depression. The collection of the sample after the first wave of infections during the SARS-CoV2 pandemic and the non-representativeness of the investigated sample limit the study's generalizability. Highlights: Network analysis is useful to assess psychological distress in medical students. Symptoms of burnout, anxiety and depression are partly interrelated. Burnout has unique features not related to anxiety and depression. Controlling for depression and anxiety, suicidal ideation is not related with burnout.